Anaerobic biodigestion of manure from finishing pig supplemented with ractopamine over different periods - Tânia M. B. dos Santos; Paula S. F. Trevizan; Cristiane A. N. Xavier; Charles Kiefer; André L. J. Ferraz (Engenharia Agrícola, 2016)
ABSTRACT This study aimed to evaluate the efficiency of anaerobic digestion and biogas production by manure from pig supplemented with ractopamine over different periods. We used manure of 50 finishing pigs according to the following diets: without supplementation and supplemented with 20-ppm ractopamine during 7, 14, 21, 28 and 35 days pre-slaughter. Continuous bench biodigesters were used in the experiment. We measured biogas production and made analyses of total (TS) and volatile solids (VS), pH, total phosphorus (total P), total nitrogen (total N) and ammoniacal nitrogen (ammoniacal N) in samples of manure, affluent and effluent from biodigesters. The pH and ammoniacal N as indicator parameters of the process balance and stability were satisfactory. Moreover, there was no difference in the reduction of TS and VS (50.04 and 56.51%, respectively). Manure of animals supplemented with ractopamine for 35 and 28 days presented higher biogas production (0.0722 and 0.0603 m3 kg−1, respectively). The supplementation with 20-ppm ractopamine for finishing pigs from 7 to 35 days does not present collapse risks for the anaerobic biodigestion process.